The Share of the Costs of Insurance Activity in the Premium of the Companies of Division II in Poland - Szymańska, Anna (Journal of Finance and Financial Law, 2020)
The costs of insurance activity in the financial reporting of insurance companies are included in technical costs, which constitute more than 90% of insurers’ costs. These costs are, on the one hand, one of the factors influencing the amount of the insurance premium, and on the other hand, they strongly influence the financial result of the insurer. The paper analyzes the costs of insurance activity of Section II insurance companies in the years 2009–2018. The analysis was based on PIU data. Statistical market norms were set for cost indicators: insurance, administrative and acquisition activities. The correlation between the the share of the insurer in the market and insurance cost index was assessed.